2010
DOI: 10.1209/0295-5075/91/20001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a deformable self-propelled domain

Abstract: We investigate the dynamical coupling between the motion and the deformation of a single selfpropelled domain based on two different model systems in two dimensions. One is represented by the set of ordinary differential equations for the center of gravity and two tensor variables characterizing deformations. The other is an active cell model which has an internal mechanism of motility and is represented by the partial differential equation for deformations. Numerical simulations show a rich variety of dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 26 publications
2
63
0
Order By: Relevance
“…The decomposition of hydrogen peroxide (2H 2 O 2 → 2H 2 O + O 2 ) proceeds on the surface of the Pt particles, which leads to non-Brownian motion of the particles. After the convection calmed down (a few minutes), we observed the movement of the Pt particles and their aggregates in hydrogen peroxide water at room temperature (20)(21)(22)(23)(24)(25) • C) using an optical microscope (Olympus IX71, Olympus Co.) and a high-speed CCD (charge-coupled device) camera (120 frames/s). O 2 microbubbles were not observed on the surface of the Pt particles or aggregates, and the bulk concentrations of hydrogen peroxide remained unchanged during the observation, although macroscopic bubbles appeared on the surface of the bulk hydrogen peroxide solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition of hydrogen peroxide (2H 2 O 2 → 2H 2 O + O 2 ) proceeds on the surface of the Pt particles, which leads to non-Brownian motion of the particles. After the convection calmed down (a few minutes), we observed the movement of the Pt particles and their aggregates in hydrogen peroxide water at room temperature (20)(21)(22)(23)(24)(25) • C) using an optical microscope (Olympus IX71, Olympus Co.) and a high-speed CCD (charge-coupled device) camera (120 frames/s). O 2 microbubbles were not observed on the surface of the Pt particles or aggregates, and the bulk concentrations of hydrogen peroxide remained unchanged during the observation, although macroscopic bubbles appeared on the surface of the bulk hydrogen peroxide solution.…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative analysis of the aggregate shape is necessary to describe the relationship between morphology and the motion type. Aggregate shape is characterized in two dimensions by a method similar to that of Hiraiwa et al 20 R(θ ) is the length between the center of gravity and the edge at angle θ (−π ≤ θ ≤ π ) from a certain axis tilted at angle ψ (0 ≤ ψ ≤ π ) in a counterclockwise direction (see Fig. 4 …”
Section: Analysis Of the Aggregate Shapementioning
confidence: 99%
“…In particular, the coupling between deformation and spontaneous motion has been actively investigated and several important and interesting studies, both experimental and theoretical, have been reported. For example, Ohta et al proposed a generic model for the coupling between deformation and spontaneous motion by analyzing such coupling from the viewpoint of the bifurcation theory of dynamical systems [1][2][3]. Teramoto et al studied the coupling between deformation and motion in pulse propagation in a reaction-diffusion system [4].…”
mentioning
confidence: 99%
“…For example, the effect of the shape on the motion of self-propelled objects without gradient sensing has been investigated extensively [19,20]. The gradient sensing ability can also be sensitive to the cell shape [21,14,15].…”
Section: Taking Cell Shape Into Accountmentioning
confidence: 99%